Ответы и объяснения

2014-03-05T23:33:58+04:00
Х²+у²-2ху=4
х+у=6
(х-у)²=4
х-у=+-2
х₁=2+у
х₂=-2+у
2+у+у=6
2у₁=4
у₁=2
-2+у+у=6
2у₂=8
у₂=4



2014-03-05T23:35:58+04:00
a^2+b^2=a^2+2ab-2ab+b^2=(a+b)^2-2ab \\&#10;x^2+y^2=2(xy+2) \ \ <=> \ \ (x+y)^2-2xy=2xy+4 \\&#10;36=4xy+4 \ \ =>  \ \ xy=8 \\&#10; \left \{ {{xy=8} \atop {x+y=6}} \right.  \ \ => \ \ (6-y)y=8 \ \ => \ \ \left \{ {{(2,4)} \atop {(4,2)}} \right.

 \frac{x^2-y^2}{xy}= \frac{5}{6}   \ \=> \ \ \frac{5}{xy} = \frac{5}{6}  \ \ => \ \ xy=6 \\&#10; \left \{ {{x^2-y^2=5} \atop {xy=6}} \right. \ \ => \ \  x= \frac{6}{y} \\&#10; \frac{36}{y^2}-y^2=5 \ \ => \ \ y^4+5y^2-36=0 \ \ => \\&#10;=> (y^2+9)(y^2-4)=0 \ \ => \ \ y \in \{-2,2\} \ \=> \ \  \left \{ {{(-3,-2)} \atop {(3,2)}} \right.
В круглых скобках ответы-координаты (x,y). Уточняю на всякий случай...